Differential Activation of Vascular Smooth Muscle Kv7.4, Kv7.5, and Kv7.4/7.5 Channels by ML213 and ICA-069673 - Brueggemann, Lyubov I. (The American Society for Pharmacology and Experimental Therapeutics, 2014)
Recent research suggests that smooth muscle cells express Kv7.4 and Kv7.5 voltage-activated potassium channels, which contribute to maintenance of their resting membrane voltage. New pharmacologic activators of Kv7 channels, ML213 (N-mesitybicyclo[2.2.1]heptane-2-carboxamide) and ICA-069673 N-(6-chloropyridin-3-yl)-3,4-difluorobenzamide), have been reported to discriminate among channels formed from different Kv7 subtypes. We compared the effects of ML213 and ICA-069673 on homomeric human Kv7.4, Kv7.5, and heteromeric Kv7.4/7.5 channels exogenously expressed in A7r5 vascular smooth muscle cells. We found that, despite its previous description as a selective activator of Kv7.2 and Kv7.4, ML213 significantly increased the maximum conductance of homomeric Kv7.4 and Kv7.5, as well as heteromeric Kv7.4/7.5 channels, and induced a negative shift of their activation curves. Current deactivation rates decreased in the presence of the ML213 (10 μM) for all three channel combinations. Mutants of Kv7.4 (W242L) and Kv7.5 (W235L), previously found to be insensitive to another Kv7 channel activator, retigabine, were also insensitive to ML213 (10 μM). In contrast to ML213, ICA-069673 robustly activated Kv7.4 channels but was significantly less effective on homomeric Kv7.5 channels. Heteromeric Kv7.4/7.5 channels displayed intermediate responses to ICA-069673. In each case, ICA-069673 induced a negative shift of the activation curves without significantly increasing maximal conductance. Current deactivation rates decreased in the presence of ICA-069673 in a subunit-specific manner. Kv7.4 W242L responded to ICA-069673-like wild-type Kv7.4, but a Kv7.4 F143A mutant was much less sensitive to ICA-069673. Based on these results, ML213 and ICA-069673 likely bind to different sites and are differentially selective among Kv7.4, Kv7.5, and Kv7.4/7.5 channel subtypes.